2010
DOI: 10.1121/1.3257202
|View full text |Cite
|
Sign up to set email alerts
|

Depth dependent variation of the echolocation pulse rate of bottlenose dolphins (Tursiops truncatus)

Abstract: Trained odontocetes appear to have good control over the timing (pulse rate) of their echolocation clicks; however, there is comparatively little information about how free-ranging odontocetes modify their echolocation in relation to their environment. This study investigates echolocation pulse rate in 14 groups of free-ranging bottlenose dolphins (Tursiops truncatus) at a variety of depths (2.4-30.1 m) in the Gulf of Mexico. Linear regression models indicated a significant decrease in mean pulse rate with mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 39 publications
1
22
0
1
Order By: Relevance
“…In comparison, the typical mean ICIs of bottlenose dolphins in the wild may be two to four times longer (Wahlberg et al, 2011). Assuming a lag time of 20 ms (Morozov et al, 1972;Au, 1993), the mean ICIs found for botos correspond to an upper search distance averaging just 11 m (sound speed: 1500 m s −1 ), whereas the mean ICI of 63-120 ms measured for two species of bottlenose dolphin (Wahlberg et al, 2011) corresponds to upper search distances from 32-75 m, conforming with other studies investigating active biosonar ranges (Au et al, 2007;Simard et al, 2010). We therefore conclude that botos operate a shortrange biosonar system, which may be reflected in their behaviour by their relatively slow swim speeds of usually less than 1 m s −1 (Best and da Silva, 1989).…”
Section: Fast Biosonar Sampling Ratessupporting
confidence: 50%
“…In comparison, the typical mean ICIs of bottlenose dolphins in the wild may be two to four times longer (Wahlberg et al, 2011). Assuming a lag time of 20 ms (Morozov et al, 1972;Au, 1993), the mean ICIs found for botos correspond to an upper search distance averaging just 11 m (sound speed: 1500 m s −1 ), whereas the mean ICI of 63-120 ms measured for two species of bottlenose dolphin (Wahlberg et al, 2011) corresponds to upper search distances from 32-75 m, conforming with other studies investigating active biosonar ranges (Au et al, 2007;Simard et al, 2010). We therefore conclude that botos operate a shortrange biosonar system, which may be reflected in their behaviour by their relatively slow swim speeds of usually less than 1 m s −1 (Best and da Silva, 1989).…”
Section: Fast Biosonar Sampling Ratessupporting
confidence: 50%
“…The spectra of extreme off-axis clicks were also published [315]. While click rates are listed in many publications, these can depend on the depth of the animal during a foraging dive [316].…”
Section: Tursiops Truncatus-bottlenose Dolphinmentioning
confidence: 99%
“…Some aspects of the acoustic behavior of echolocating free-ranging bottlenose dolphins have been described already by Norris (1967Norris ( , 1969. More recent and detailed information has been provided by Jensen et al (2009b) for T. aduncus and Simard et al (2009) for T. truncatus. However, some of the basic source parameters of the clicks from freeranging bottlenose dolphins are still unknown, despite the bottlenose dolphin being the most studied of all cetacean species.…”
mentioning
confidence: 99%